1974
DOI: 10.1084/jem.139.5.1175
|View full text |Cite
|
Sign up to set email alerts
|

RECEPTORS FOR AGGREGATED IgG ON MOUSE LYMPHOCYTES

Abstract: An autoradiographic binding assay employing 125I-labeled heat-aggregated mouse IgG2b myeloma protein (MOPC 141) was used to demonstrate receptors for IgG on 20–45% of Balb/c thymocytes and on 70–80% of splenocytes. Binding could also be shown with heat or BDB aggregates of another IgG2b (MOPC 195), with IgG1 and with human γ-globulin, but not with aggregated chicken γ-globulin, IgA, BSA, nor with aggregated Fab fragments of IgG2b. Optimum binding was obtained at 37°C. Detection of binding was dependent upon ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
30
1

Year Published

1975
1975
1983
1983

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(33 citation statements)
references
References 18 publications
2
30
1
Order By: Relevance
“…Both alloantigen and Con A activation of T lymphocytes induce or enhance the expression by these cells of Fc receptors (17)(18)(19)(20) and Ia alloantigens (10, 20). Lack of B-cell adsorption, as well as genetic restriction of suppressor-target interaction suggest that Fc receptors are not a primary component of the suppressor target structure.…”
Section: Discussionmentioning
confidence: 99%
“…Both alloantigen and Con A activation of T lymphocytes induce or enhance the expression by these cells of Fc receptors (17)(18)(19)(20) and Ia alloantigens (10, 20). Lack of B-cell adsorption, as well as genetic restriction of suppressor-target interaction suggest that Fc receptors are not a primary component of the suppressor target structure.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the T lymphocytes do not need to be in an activated state to express the Fc receptor . Secondly, only 50-60% of the large "activated" T cells bear the Fc receptor (7)(8)(9), suggesting that activation does not always lead to acquisition of the Fc receptor. Finally, it was reported that KLH-activation of T lymphocytes resulted in a substantial increase in Fc+ T cells (8) .…”
mentioning
confidence: 99%
“…Graded numbers of these 1 wk KLH-primed T lymphocytes were then transferred into lethally irradiated syngeneic recipients along with 100 jig DNP-KLH and 5 x 10' anti-theta plus complement-treated spleen cells from (SJL x BALB)F, mice primed 1 mo previously with 100 Wg alum- Several groups have recently reported that the Fe receptor appears on T lymphocytes activated by exposure to KLH (8) or allogeneic cells (7,9). We have also found an increase in the number of Fc+ T cells as a result of allogeneic activation (unpublished observation).…”
mentioning
confidence: 99%
“…To this mixture, 3-10 × l0 s cells in 0.3 ml were added. Incubation with intermittent agitation proceeded for 60 min at 4°C for macrophage-like cells and at 37°C for all other cells (7). The amount of radiolabeled IgG bound by the cells was determined by layering 0.2 ml of the reaction mixture on top of 1 ml cold fetal calf serum (FCS) in 1.5 ml conical polyethylene tubes and separating unbound from cell-associated IgG by centrifuging the cells through the FCS at 350 g for 8 min.…”
mentioning
confidence: 99%